Arrangement, listening, and the music of Gérard Pesson - Drummond, WJ (2019)
This thesis develops a critical framework for the study of musical arrangement and its relationship with concepts of listening through interpretations of music by Gérard Pesson (born 1958). It begins by identifying and accounting for persistent interpretative reflexes in existing discussions of arrangement, arguing that arrangement is best understood not as a type of musical object defined by fidelity to an original but rather as a way of listening influenced by this and other concepts. The four case studies that follow explore different implications of this shift in critical perspective, combining close reading and listening, philosophical reflection (in particular insights offered by conceptual metaphor theory and figures including Bergson, Sartre, and Adorno), and studies of reception. The first case study displaces the ‘original’ as the primary source of an arrangement’s significance, arguing that Nebenstück (1998) plays extensively on the meanings of medium, through the manipulation of timbre and noise. The second considers the idea of linear temporal fidelity to a source as an engagement with notions of structural listening, using an examination of Ambre Nous Resterons (2008) to demonstrate that such fidelity is not a condition of arrangement but an ideal from which arrangements might meaningfully depart. The third complicates the relationship between the timbral and temporal aspects of arrangement discussed in the previous two chapters, exploring how Pesson manipulates both aspects in Wunderblock (2005) to suggest the absence rather than re-presentation of a source. The fourth probes the fraught relationship between notions of arrangement, fidelity, and kitsch within the overlapping contexts of modernism and historical ‘authenticity’, analysing the discourses surrounding Kein Deutscher Himmel (1997) supplied by Pesson himself, the transcription’s commercial distribution, and a variety of its listeners. Finally, this thesis considers the extent to which musical arrangements, in particular those of Pesson, might be interpreted as offering ‘critical’ perspectives on listening.